Las artes plásticas como desarrollo de la motricidad fina de niñas y niños de primer grado de educación general básica en la Escuela Juan Montalvo, del cantón Pasaje 2014-2015 - Fárez Llivisupa, Mayra Alejandra (2015)
The development of the present design of research was orientated in function to THE PLASTIC ARTS AS FINE MOTOR DEVELOPMENT OF GIRLS AND CHILDREN THE FIRST DEGREE OF BASIC GENERAL EDUCATION IN SCHOOLS JUAN MONTALVO with the purpose of understanding the reality in which the child is immersed and updating the knowledge of teachers as for the use of new techniques that help improve the development of motor skills of children from 5 to 6 years old, creating a suitable and creative environment, using the analytical method.